STRATEGIES FOR IMPROVING LECTURER PERFORMANCE AFFECTED BY SEVERAL FACTORS WITH JOB SATISFACTION AS AN INTERVENING VARIABLE IN PRIVATE HIGHER EDUCATION INSTITUTIONS IN EAST JAVA - Moh Azus shony Azar; Nur Sayidah; Liosten Rianna Roosida Ully Tampubolon (International Journal of Economic Integration and Regional Competitiveness, 2025)
Objective: This study aims to analyze strategies for improving the performance of lecturers in private universities in East Java by examining various factors, with job satisfaction as an intervening variable. Method: The research employs path analysis with Structural Equation Modeling (SEM) using PLS version 3.4.1. The population consists of 5,670 lecturers, and using the Slovin formula, a sample of 98 respondents was obtained. Results: The findings indicate that: (1) Total Quality Management positively and significantly influences lecturers' job satisfaction (p-value = 0.000 < 0.05), (2) Organizational Justice positively and significantly influences job satisfaction (p-value = 0.001 < 0.05), (3) Quality of Work Life positively and significantly influences job satisfaction (p-value = 0.000 < 0.05), (4) Person-Organization Fit (P-O Fit) positively and significantly influences job satisfaction (p-value = 0.009 < 0.05), (5) Job satisfaction positively and significantly influences lecturers' performance (p-value = 0.028 < 0.05), (6) Total Quality Management positively and significantly influences lecturers' performance (p-value = 0.022 < 0.05), (7) Organizational Justice positively and significantly influences lecturers' performance (p-value = 0.012 < 0.05), (8) Quality of Work Life positively and significantly influences lecturers' performance (p-value = 0.010 < 0.05), and (9) Person-Organization Fit positively and significantly influences lecturers' performance (p-value = 0.007 < 0.05). Novelty: This study highlights the crucial role of Total Quality Management, Organizational Justice, Quality of Work Life, and Person-Organization Fit in enhancing job satisfaction, which in turn improves lecturers' performance. The findings underscore the importance of recognizing practical lecturers and research achievements as key factors in fostering job satisfaction and performance in private universities in East Java.